A Radiographic Classification of Massive Rotator Cuff Tear Arthritis - Hamada, Kazutoshi (Springer-Verlag, 2011)
BACKGROUND: In 1990, Hamada et al. radiographically classified massive rotator cuff tears into five grades. Walch et al. subsequently subdivided Grade 4 to reflect the presence/absence of subacromial arthritis and emphasize glenohumeral arthritis as a characteristic of Grade 4. QUESTIONS/PURPOSES: We therefore determined (1) whether patient characteristics and MRI findings differed between the grades at initial examination and final followup; (2) which factors affected progression to a higher grade; (3) whether the retear rate of repaired tendons differed among the grades; and (4) whether the radiographic grades at final followup differed from those at initial examination among patients treated operatively. PATIENTS AND METHODS: We retrospectively reviewed 75 patients with massive rotator cuff tears. Thirty-four patients were treated nonoperatively and 41 operatively. RESULTS: Patients with Grade 3, 4, or 5 tears had a higher incidence of fatty muscle degeneration of the subscapularis muscle than patients with Grade 1 or 2 tears. In 26 patients with Grade 1 or 2 tears at initial examination, duration of followup was longer in patients who remained at Grade 1 or 2 than in those who progressed to Grade 3, 4, or 5 at final followup. The retear rate of repaired supraspinatus tendon was more frequent in Grade 2 than Grade 1 tears. In operated cases, radiographic grades at final followup did not develop to Grades 3 to 5. CONCLUSIONS: We believe cuff repair should be performed before acromiohumeral interval narrowing. Our observations are consistent with the temporal concepts of massive cuff tear pathomechanics proposed by Burkhart and Hansen et al. LEVEL OF EVIDENCE: Level III, Therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.